2012
DOI: 10.5897/ajar11.896
|View full text |Cite
|
Sign up to set email alerts
|

Red palm weevil (Rhynchophorus ferrugineus Olivier) infestation and its chemical control in Sindh province of Pakistan

Abstract: The survey on various parameters showed that the degree of orchard infestation fluctuated by time period/seasons, so attack of red palm weevil varied on different months of the year during the study period. It was observed that this insect pest had significantly higher (16%) infestation in the months of June, July and August, during experimental period. The least attack (8%) of the weevil was in the months of January, September, October, November and December in both the years (2007 and 2008). Place of infesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Currently, the primary strategy for controlling this pest is through the use of chemical pesticides. Unfortunately, increasing evidence has shown that R. ferrugineus has strong resistance to a variety of commonly used pesticides [ 2 , 3 ]. In the perspective of sustainable development, it is emergent to invent a novel alternative management strategy to fight against this pest.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the primary strategy for controlling this pest is through the use of chemical pesticides. Unfortunately, increasing evidence has shown that R. ferrugineus has strong resistance to a variety of commonly used pesticides [ 2 , 3 ]. In the perspective of sustainable development, it is emergent to invent a novel alternative management strategy to fight against this pest.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, chlorantraniliprole exhibited an LC50 of 6 mg ai L −1 against boll weevil adults, Anthonomus grandis Boheman [14]. Red palm weevil larvae, Rhynchophorus ferrugineus Olivier, demonstrated susceptibility to spirotetramat, leading to a recovery of approximately 65% of damaged trees 60 days after being injected into the trunk [15]. Furthermore, when flupyradifurone was administered via trunk injection in oil palm hosts, it resulted in larval mortality of at least eight times higher than when applied through spraying [16].…”
Section: Introductionmentioning
confidence: 99%
“…These insecticides belong to different groups such as carbamate, organophosphate, organochlorine, phenylpyrazole, neonicotinoid and macrocyclic lactone (Abraham et al, 1998;Ajlan et al, 2000;Abo-El-Saad et al, 2001;Al-Rajhi et al, 2005;Al-Shawaf et al, 2010;Abo-El-Saad et al, 2011;Al-Jabr et al, 2013). Insecticides which have been tested in other laboratories and/or in field experiments worldwide include spirotetramat, azadirachtin, aluminum phosphide, methidathion and oxamyl against all stages of RPW (Cabello et al, 1997;Kaakeh, 2006;Llacer and Jacas, 2010;Shar et al, 2012;Shawir et al, 2014;Alhewairini, 2018).…”
Section: Introductionmentioning
confidence: 99%